2011
DOI: 10.1111/j.1745-4530.2010.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Pectin‐based Edible Coating for Shelf‐life Extension of Ataulfo Mango

Abstract: Mango is a commercial but highly perishable fruit, and therefore, a longer shelf life is necessary for its successful marketing and consumer satisfaction. This study aims at evaluating the effects of edible coating, based on pectin, on the quality and shelf‐life extension of mangoes. The coating formulations included different combinations of pectin, beeswax, sorbitol and monoglyceride. The fruits were coated and stored at room temperature along with uncoated controls. Samples tested were evaluated periodicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 40 publications
7
49
0
11
Order By: Relevance
“…The delay in changes on texture and color was observed, concluding that pectin coatings could extend the shelf-life of avocados to over a month at 10 °C. Similar results were reported by Moalemiyan et al in fresh-cut mangoes coated with pectins, which remained in acceptable quality conditions for over two weeks by applying the optimized coating formulation: pectin (1.3% in water), sorbitol (28%) as plasticizer and beeswax (23%) based on pectins dry weight [67]. Authors reported that some optimization of the coating formulation was necessary to prevent the off-flavor development and the anaerobic respiration.…”
Section: Shelf-life Extension Of Fresh-cut Fruits and Vegetablessupporting
confidence: 81%
“…The delay in changes on texture and color was observed, concluding that pectin coatings could extend the shelf-life of avocados to over a month at 10 °C. Similar results were reported by Moalemiyan et al in fresh-cut mangoes coated with pectins, which remained in acceptable quality conditions for over two weeks by applying the optimized coating formulation: pectin (1.3% in water), sorbitol (28%) as plasticizer and beeswax (23%) based on pectins dry weight [67]. Authors reported that some optimization of the coating formulation was necessary to prevent the off-flavor development and the anaerobic respiration.…”
Section: Shelf-life Extension Of Fresh-cut Fruits and Vegetablessupporting
confidence: 81%
“…Kittur et al (2001), Zhu et al (2008), serta Moalemiyan et al (2011) melaporkan bahwa penggunaan pelapis berbasis polisakarida efektif untuk menghambat laju respirasi, kehilangan kekerasan, perubahan warna, serangan C. gloeosporioides serta menurunkan pembentukan asam askorbat pada mangga.…”
Section: Abstrakunclassified
“…Penambahan komponen lemak seperti beeswax diketahui dapat meregulasi keseimbangan komponen hidrofilik-hidrofobik pelapis sehingga meningkatkan efektifitasnya dalam menekan kehilangan air. Penelitian serupa melaporkan bahwa pelapisan mangga menggunakan kombinasi polisakarida (pektin) dan lemak (beeswax) mampu menurunkan susut bobot mangga lebih kecil (4.4 %) dibanding kontrol (6.3 %) setelah 6 hari penyimpanan (Moalemiyan et al 2011). Gambar 1 juga menunjukkan bahwa penambahan NP-ZnO pada pelapis (perlakuan N1B0) mampu menurunkan susut bobot lebih kecil dibanding kontrol dan N0B0 (α = 5 %).…”
Section: Susut Bobotunclassified
See 2 more Smart Citations